Antioxidant, antibacterial, anti-inflammatory, and anticancer properties of Cinnamomum kanehirae Hayata leaves extracts - Po-Hsien Li; Yun-Jhen Shih; Wen-Chien Lu; Ping-Hsiu Huang; Chiun-Chuang R. Wang (Arabian Journal of Chemistry, 2023)
Bull Camphor tree (Cinnamomum kanehirae Hayata; CKH) (Lauraceae) is an endemic species in Taiwan. Its trunk is the main host of Taieanofugus camphoratus, traditional medical fungi. There are few research involving the functional properties and antibacterial activity of Cinnamomum kanehirae Hayata leaves (CKHL), although its abundant leaves. The purpose of the study was to investigate the effects of the different concentrations of ethanol solvents on the chemical compositions and biological activities of the CKHL extract (CKHLE). Furthermore, the antioxidant, antibacterial activity, anti-inflammatory, and anticancer ability of the extracts were tested. The results showed that the 50% ethanol CKHLE indicated the highest total polyphenols (TPC) and total flavonoids (TFC) (16.98 ± 0.18 mg GAE/g and 1.90 ± 0.04 mg QE/g, respectively) among the CKHLEs. The 50% ethanol CKHLE also indicated the best antioxidant performance in DPPH and ABTS+ free radical scavenging, reducing power, and ferric reducing antioxidant power (FRAP). The antioxidant performance of the four CKHLEs were exhibited in a dose-dependent manner. As well as, the 95% ethanol extract CKHLE indicated moderate antibacterial activity against Candida albicans, Escherichia coli, and Bacillus cereus. In terms of anti-inflammatory ability, all CKHLEs showed the best COX-2 inhibition at the concentration of 10 mg/mL. The 80% ethanol CKHLE reduced by 50.05% of NO production in Raw 264.7 cells compared to the control. The 80% and 95% CKHLEs also exhibited decreases in cell viability of colorectal cancer cells (C2BBe1) up to 94.64% and 93.99%, respectively, at the CKHLE’s concentration of 1000 μg/mL. These results demonstrated the different solvents affected the chemical compositions and biological activities (antibacterial, antioxidant, anti-inflammatory and anticancer activities) of CKHLE. Furthermore, the CKHLE are a potential source of healthy foods, bacteriostatic and non-steroidal anti-inflammatory drugs (NSAIDs) development.